Functional differences between alien and native species: do biotic interactions determine the functional structure of highly invaded grasslands? - Luca Borger (Functional Ecology, 2013)
1. Although observed functional differences between alien and native plant species support the idea that invasions are favoured by niche differentiation (ND), when considering invasions along large ecological gradients, habitat filtering (HF) has been proposed to constrain alien species such that they exhibit similar trait values to natives. 2. To reconcile these contrasting observations, we used a multi-scale approach using plant functional traits to evaluate how biotic interactions with native species and grazing might determine the functional structure of highly invaded grasslands along an elevation gradient in New Zealand. 3. At a regional scale, functional differences between alien and native plant species translated into non-random community assembly and high ND. Alien and native species showed contrasting responses to elevation and the degree of ND between them decreased as elevation increased, suggesting a role for HF. At the plant-neighbourhood scale, species with contrasting traits were generally spatially segregated, highlighting the impact of biotic interactions in structuring local plant communities. A confirmatory multilevel path analysis showed that the effect of elevation and grazing were moderated by the presence of native species, which in turn influenced the local abundance of alien species. 4. Our study showed that functional differences between aliens and natives are fundamental to understand the interplay between multiple mechanisms driving alien species success and their coexistence with natives. In particular, the success of alien species is driven by the presence of native species which can have a negative (biotic resistance) or a positive (facilitation) effect depending on the functional identity of alien species.